Economic impact of cooperative membership on dairy farmers in Manipur: a propensity score matching approach - Laishram Priscilla; A K Chauhan (Agricultural Economics Research Review, 2023)
This study assesses the impact of dairy cooperatives on yield, technical efficiency and price of milk, and also on income and employment levels using the propensity score matching (PSM) technique. The findings show that dairy cooperatives did not make any significant contribution in improving milk yield, technical efficiency, price and net income in Manipur. However, these helped employment generation for the dairy households in the state. This indicates inherent weaknesses in the functioning of dairy cooperatives and suggests the need for strengthening forward and backward linkages for providing adequate support services to the member farmers.